Проблеми і методи впровадження міжнародних стандартів забезпечення інформаційної безпеки - Красюкова, В. В. (ХНУРЕ, 2023)
Ensuring information security is one of the most important tasks of the modem world. Every year, the amount of digital data processed by companies and organizations increases, so it is important to protect this information from unauthorized access. To achieve this goal, international standards for ensuring information security were developed. For successful implementation, it is necessary to use different methods and take into account the specifics of the specific organization and the context in which it operates. For successful implementation, it is necessary to use different methods and take into account the specificities of the specific organization and the context in which it operates.